Meeting the productivity challenge below 2.5 kilometres - Morrison, D. (UMT 2017: Proceedings of the First International Conference on Underground Mining Technology, 2017)
The major trends in the global mining industry are well established and will continue; more metal resources are being produced from underground mines than from surface mines, grades are declining in many mines, production costs are increasing as mines become deeper and hotter, and the rate of discovery of new mines remains low. Furthermore, even those mines that are discovered will be ever more remote from the infrastructure that connects them to the market – adding the extra cost of transportation from infrastructure to market, to the cost of production. This increases the requirement for higher profitability. In addition to these internal industry issues, the external pressure will continue to increase and intensify; the public’s demand for greater protection of the environment, especially northern sensitive ecologies, will intensify along with the desire to see populations living close to mines to enjoy greater share of the benefits from mines. The external pressures are relatively new but the internal trends have been with us for several years and industry has been slow to respond. However, the slow recovery means all these factors must be addressed; but for all these demands to be met and for declining performances to be reversed, major changes in the way mines operate have to occur. Simply waiting for an increase in commodity prices is not a viable option – there are few indications that rapid increases will happen, and in any event, costs are likely to escalate at least at the same rate. The demographics of the industry are going to change very rapidly – much faster than the typical 25% replacement rate. The real problem is that experience will be lost at a rate far greater than individuals, because experienced retirees are replaced by relative novices. This will inevitably lead to poorer planning, more errors and subsequent cost increases that will accelerate with time. Continuing to use the ‘experience-intensive’ processes we use today is a recipe for very poor financial performance, both in new project implementation and in routine operations. We believe that new communications, digital and analytical technologies, supplied by sensor data and managed by artificial intelligence will not decrease employment in mines; we believe these technologies will be essential for mines to cope with the rapid decrease in the number of experienced employees. It is 35 years since the last major transformation in productive technology. The next change is long overdue, and although improved data management and digital mining will help, it is simply not sufficient. Yes, we can use software to improve several aspects of daily operations. We can use drones to assess the stability conditions in open stopes and orepasses. There are probabilistic models for optimising the best and most robust of thousands of production planning options – SOT Plus is one example. But in the end, the business of mining is breaking and moving many thousands of tonnes of rock every day, and unless there are major changes in the way we do this, many operations may not be able to survive the future commodity price projections. Since more than 95% of the material mines produce is waste, we need to demonstrate and assure the public that we can be relied upon to provide a far higher level of environmental stewardship than before, and our approach to water usage and water management has to change dramatically. This is the only way to reduce the time to mine permit and social license to operate. And, finally, we have to develop technology that will decrease the cost and risk of finding new mines and enabling industrial-scale developments in very remote locations. Without these changes, many mines around the world will not be fit for purpose in the next decade. When problems seem to be intractable to more and more focus, it is often valuable to change the perspective – look further afield – in space and time. Some of our best ideas come from looking at how things are done in different places, in different industries and, most importantly, in earlier times. The solutions developed to circumvent the limitations of pre-industrial society and early industrialisation have lessons to teach us. In many cases, the ideas that are currently being considered as the primary target for innovation tend to focus on costs – reducing the direct cost of labour through automation, or reducing the cost of ventilation by eliminating diesel particulates. The other important factor, which is too often over-looked, is time; the time to find the next orebody, the time to first production, the time to obtain a mining permit, the time necessary to obtain social licence to operate. All these delays have been increasing and it is sometimes worth spending a little more money to gain a lot of time. Just as we need to work on ideas that reduce the cost of doing things, we must also work on ideas that reduce the time it takes to get things done, and get them done better.